2022
DOI: 10.3389/fcvm.2022.953657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi on health status in adults with chronic heart failure: A systematic review and meta-analysis

Abstract: BackgroundChronic heart failure (CHF) is among the top causes of cardiovascular morbidity, and most patients with CHF have poor health status. Tai Chi, a mind-body exercise that originated in China, is beneficial for health status. This study was conducted to evaluate the effects of Tai Chi on health status in adults with CHF.MethodsThe Cochrane Library, PubMed, Embase, Web of Science, China National Knowledge Infrastructure, Wanfang Database, Chinese Biomedical Database, and Chinese Scientific Journal Databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Multiple meta-analyses showed that heart failure patients took Tai Chi rehabilitation exercise on the basis of conventional drug treatment. After 6 months of treatment, quality of life, cardiac function grading, 6MWD, LVEF, and LVEDD in the treatment group was significantly better than that of the control group (72,73). Clinical research (74,75) reported that, compared with taking conventional drugs alone, conventional Western medicine combined with Ba Duan Jin's comprehensive treatment can significantly improve patients' BNP, metabolic equivalents (METs), maximum oxygen consumption (VO 2 Max), 6MWD, New York Heart Association (NYHA) classification, LVEF, TCM symptoms, quality of life, and other indicators, and the degree of improvement is obviously better than that of the control group.…”
Section: Other Traditional Alternative Strategies For Rhf Treatmentmentioning
confidence: 84%
“…Multiple meta-analyses showed that heart failure patients took Tai Chi rehabilitation exercise on the basis of conventional drug treatment. After 6 months of treatment, quality of life, cardiac function grading, 6MWD, LVEF, and LVEDD in the treatment group was significantly better than that of the control group (72,73). Clinical research (74,75) reported that, compared with taking conventional drugs alone, conventional Western medicine combined with Ba Duan Jin's comprehensive treatment can significantly improve patients' BNP, metabolic equivalents (METs), maximum oxygen consumption (VO 2 Max), 6MWD, New York Heart Association (NYHA) classification, LVEF, TCM symptoms, quality of life, and other indicators, and the degree of improvement is obviously better than that of the control group.…”
Section: Other Traditional Alternative Strategies For Rhf Treatmentmentioning
confidence: 84%
“…Practicing tai chi can promote the movement of qi throughout the body using a combination of meditation, slow and gentle movements, as well as breathing and relaxation techniques [90]. A recent systematic review of 15 studies concluded that the addition of tai chi to standard care improved LVEF and NT-proBNP levels and reduced MLHFQ scores and hospitalization risk for HF [91]. Another study found that tai chi can reduce depression scores [92] and significantly improve the quality of life and exercise capacity, as measured by the 6MWT [92].…”
Section: Tai Chimentioning
confidence: 99%
“… 45 Similar conclusions were drawn by Hui et al, who found that Tai Chi Chuan alleviated depressive symptoms and improved sleep quality, with no significant impact on VO 2peak . 46 Redwine et al investigated a 16-week Tai Chi Chuan exercise program, observing noteworthy reductions in depressive symptoms in comparison to conventional treatment. 47 Nevertheless, no noticeable disparities in the 6-minute walk distance (6MWD) were seen, which could be attributed to constraints such as the relatively small number of participants, the elderly age of the individuals involved, and the existence of other medical conditions that would have hindered their ability to walk.…”
Section: Traditional Mind-body Exercisementioning
confidence: 99%